2015
DOI: 10.1021/acs.langmuir.5b03221
|View full text |Cite
|
Sign up to set email alerts
|

Drug–Polymer Electrostatic Complexes as New Structuring Agents for the Formation of Drug-Loaded Ordered Mesoporous Silica

Abstract: Using aminoglycoside antibiotics as drug models, it was shown that electrostatic complexes between hydrophilic drugs and oppositely charged double-hydrophilic block copolymers can form ordered mesophases. This phase behavior was evidenced by using poly(acrylic acid)-block-poly(ethylene oxide) block copolymers in the presence of silica precursors, and this allowed preparing drug-loaded mesoporous silica directly from the drug-polymer complexes. The novel synthetic strategy of the hybrid materials is highly effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…Stimuli responsive double hydrophilic block copolymers (DHBCs) have attracted much interest due to their ability to form micelles in response to an external stimulus such as temperature, pH, salinity or a combination of different stimuli in aqueous solutions. [1][2][3][4] Consequently, such block copolymers display potential applications in the biomedical field as drug carrier systems, 4,5 biosensors, 6 biomimetic mineralization templates, [7][8][9] fluorescent chemosensors 10 as well as for gene therapy and in-vivo imaging/targeting. [11][12] Among the different possible structures, thermosensitive poly(ethyleneglycol)-block-poly(N-isopropylacrylamide) (PEG-b-PNIPAm) DHBCs were widely studied as they proved to be biocompatible.…”
Section: Introductionmentioning
confidence: 99%
“…Stimuli responsive double hydrophilic block copolymers (DHBCs) have attracted much interest due to their ability to form micelles in response to an external stimulus such as temperature, pH, salinity or a combination of different stimuli in aqueous solutions. [1][2][3][4] Consequently, such block copolymers display potential applications in the biomedical field as drug carrier systems, 4,5 biosensors, 6 biomimetic mineralization templates, [7][8][9] fluorescent chemosensors 10 as well as for gene therapy and in-vivo imaging/targeting. [11][12] Among the different possible structures, thermosensitive poly(ethyleneglycol)-block-poly(N-isopropylacrylamide) (PEG-b-PNIPAm) DHBCs were widely studied as they proved to be biocompatible.…”
Section: Introductionmentioning
confidence: 99%
“…This route relies on the use of a weak polyacid double hydrophilic block copolymer (DHBC) able to form polyion complex micelles upon interaction with a weak polybase. We reported that DHBCs such as poly(ethylene oxide)- b -poly(acrylic acid) (PEO- b -PAA) or poly(ethylene oxide)- b -poly(methacrylic acid) (PEO- b -PMAA) copolymers, are able to form polyion complex (PIC) micelles upon interaction with weak polybases such as oligochitosan (OC) [25], poly-L-lysine (PLL) [2627] and aminoglycoside antibiotics [28]. PIC micelles present a core–corona structure, whose core is formed by electrostatic interactions between the two charged blocks (i.e., the PAA and the weak polybase) and the corona is constituted by the neutral PEO block of the DHBC, which ensures the steric stabilization of the assembly in water.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(ethylene oxide)‐ b ‐poly(acrylic acid) (PEO‐ b ‐PAA) double‐hydrophilic block copolymers associated with an oligochitosan [OC] as the micellization agents were used as efficient templates of ordered mesoporous silica materials with tunable mesostructures. Subsequently, newly synthesized mesoporous silicas were formed using aminoglycoside antibiotics as micellizing agent, thus affording mesostructured materials directly loaded with the drug . We recently extended the use of such systems to synthesize PMOs from phenylene‐bridged organosilane ( BTEB : 1,4‐bis(triethoxysilyl)benzene) using water as solvent.…”
Section: Introductionmentioning
confidence: 99%